1968
DOI: 10.1175/1520-0493(1968)096<0477:ewasgc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Experiments With a Stratospheric General Circulation Model

Abstract: An 18-vertical level primitive equation general circulation model was developed from previous models of the Geophysical Fluid Dynamics Laboratory in order to study t,he lower stratosphere in detail. The altitude range covered was from the surface to 4 mb. (37.5 km.), the vertical resolution being optimized in the tropopause region to permit a more accurate calculation of the vertical transport terms. A polar stereographic projection waa used and the model waa limited to a single hemisphere. The model now resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The statistics of temperature and motions as a whole well agree with those of the actual atmosphere. But, as being so in this kind of models (e.g., Manabe and Hunt, 1968), the zonal means of temperature and motion resemble those observed in winter rather than those of annual mean and the activity of eddies is somewhat weaker than that in winter.…”
Section: Time Integrationmentioning
confidence: 65%
“…The statistics of temperature and motions as a whole well agree with those of the actual atmosphere. But, as being so in this kind of models (e.g., Manabe and Hunt, 1968), the zonal means of temperature and motion resemble those observed in winter rather than those of annual mean and the activity of eddies is somewhat weaker than that in winter.…”
Section: Time Integrationmentioning
confidence: 65%
“…The lack of any transports of angular momentum by the meridional cells is a feature of a quasigeostrophic model that was particularly evident in the angular momentum budget. Manabe and Hunt (1968) found the general features of the lower stratosphere to be much better simulated with a high resolution model.…”
Section: Source Of Discrepanciesmentioning
confidence: 91%
“…A deep stratosphere wind braking description with p low = 0.1 bar and k max = 1/20 days −1 furthermore reproduces the observed wind speeds (Figure 3,upper panel). See, e.g., Manabe & Hunt (1968) or the review by Haynes (2005) for comparison with the observed Earth zonal wind structure.…”
Section: Earth Benchmarking and Eddy Diagnosticsmentioning
confidence: 99%